The effect of temperature on specific dynamic action of juvenile fall-run Chinook salmon, Oncorhynchus tshawytscha. Issue 1 (27th October 2022) - Lo, Vanessa K; Martin, Benjamin T; Danner, Eric M; Cocherell, Dennis E; Cech, Jr, Joseph J; Fangue, Nann A
Abstract: Juvenile fall-run Chinook salmon ( Oncorhynchus tshawytscha ) in the Sacramento–San Joaquin River Basin experience temporally and spatially heterogenous temperature regimes, between cool upper tributaries and the warm channelized Delta, during freshwater rearing and outmigration. Limited water resources necessitate human management of dam releases, allowing temperature modifications. The objective of this study was to examine the effect of temperature on specific dynamic action (SDA), or the metabolic cost associated with feeding and digestion, which is thought to represent a substantial portion of fish energy budgets. Measuring SDA with respect to absolute aerobic scope (AAS), estimated by the difference between maximum metabolic rate (MMR) and standard metabolic rate (SMR), provides a snapshot of its respective energy allocation. Fish were acclimated to 16°C, raised or lowered to each acute temperature (13°C, 16°C, 19°C, 22°C or 24°C), then fed a meal of commercial pellets weighing 2% of their wet mass. We detected a significant positive effect of temperature on SMR and MMR, but not on AAS. As expected, there was no significant effect of temperature on the total O2 cost of digestion, but unlike other studies, we did not see a significant difference in duration, peak metabolic rate standardized to SMR, time to peak, percent of meal energy utilized, nor the ratio of peak O2 consumption to SMR. Peak O2 consumption represented 10.4–14.5% of AAS leaving a large amount of aerobic capacity available for other activities, and meal energy utilized for digestion ranged from 5.7% to 7.2%, leaving substantial remaining energy to potentially assimilate for growth. Our juvenile fall-run Chinook salmon exhibited thermal stability in their SDA response, which may play a role in maintaining homeostasis of digestive capability in a highly heterogeneous thermal environment where rapid growth is important for successful competition with conspecifics and for avoiding predation.